The topic comprehension and the informative texts idea. An experience with teachers of communication - Terrones León, Roger Ubaldo (2014)
This article has the intention to present studies from active investigation, in the National Mobilization Program for the Reading Comprehension. We treat the matter of topic comprehension and the principal idea from an informative text across the actions that we have carried out together with Basic Regular Education communication teachers in a Secondary (High School) level. We star from topic concept, the principal idea and teacher’s presentation about the topic who we work. This is the activities that we proposed and the results.